International Students’ Relationship Formation in a Multicultural Setting: A Phenomenological Inquiry - Mahlon Juma (Journal of Arts, Humanities and Social Science)
International students who do not build meaningful friendships have psychological and social issues, as well as weak academic and decision-making skills. The study investigated international students' relationship formation in a multicultural setting in the Philippines, using psychoanalytic transference theory and the functional model of friendship formation. Using transcendental phenomenology, audio-recorded one-on-one interviews were conducted with 12 enrolled students from 12 nations. The data was transcribed and analyzed. According to the findings, co-national friendships were favored for psychological and emotional support, as well as the perpetuation of home cultures. Students who favored host-national friendships over multicultural home ties reported higher levels of life satisfaction, fewer social issues, and a greater appreciation for culture. Students who favored host-national connections overcame home ties and had more life satisfaction, fewer social issues, and a greater appreciation for culture and were more likely to marry and work in host nations. Furthermore, friendships enhance one's lifestyle and psychological well-being, provide enjoyment and satisfaction, enhance critical thinking, and reduce stress as well as criminal activity. The implications of the findings were examined.